MUSLIM CONSUMERS' HALAL AWARENESS TOWARDS THE PURCHASE OF SKINCARE PRODUCTS - Moslem, Habibah; Prawiro, Atmo (Academic Solution Publisher, 2024)
The purpose of this study is to analyze the halal awareness of Muslim consumers who buy skincare products through the marketplace from the halal label printed on the most sold products because it is important for Muslims to consume and use products that are clearly halal. The research method used is a descriptive qualitative approach with liberal research analysis with secondary data. The results of this study indicate that the level of halal awareness of Muslim consumers in Indonesia is still low, as evidenced by the highest product sales in the marketplace, namely Garnier products from France that do not have a halal label. From this research it is hoped that the government, especially the halal product guarantee institution, will educate consumers about the importance of using halal skincare products to avoid things that are prohibited by Islam.